A genome-wide association study in Swedish colorectal cancer patients with gastric- and prostate cancer in relatives - Johanna Samola Winnberg; Litika Vermani; Wen Liu; Veronika Soller; Jessada Thutkawkorapin; Mats Lindblad; Annika Lindblom (Hereditary Cancer in Clinical Practice)
Abstract Background A complex inheritance has been suggested in families with colorectal-, gastric- and prostate cancer. Therefore, we conducted a genome-wide association study (GWAS) in colorectal cancer patients, who’s relatives had prostate-, and/or gastric cancer. Methods The GWAS analysis consisted of 685 cases of colorectal cancer and 4780 healthy controls from Sweden. A sliding window haplotype analysis was conducted using a logistic regression model. Thereafter, we performed sequencing to find candidate variants, finally to be tested in a nested case–control study. Results Candidate loci/genes on ten chromosomal regions were suggested with odds ratios between 1.71–3.62 and p-values < 5 × 10–8 in the analysis. The regions suggested were 1q32.2, 3q29, 4q35.1, 4p15.31, 4q26, 8p23.1, 13q33.3, 13q13.3, 16q23.3 and 22q11.21. All regions, except one on 1q32.2, had protein coding genes, many already shown to be involved in cancer, such as ZDHHC19, SYNPO2, PCYT1A, MYO16, TXNRD2, COMT, and CDH13. Sequencing of DNA from 122 colorectal cancer patients with gastric- and/or prostate cancer in their families was performed to search for candidate variants in the haplotype regions. The identified candidate variants were tested in a nested case–control study of similar colorectal cancer cases and controls. There was some support for an increased risk of colorectal-, gastric-, and/or prostate cancer in all the six loci tested. Conclusions This study demonstrated a proof of principle strategy to identify risk variants found by GWAS, and identified ten candidate loci that could be associated with colorectal, gastric- and prostate cancer. Graphical Abstract